415 Parents' Evaluation of Developmental Status (PEDS:DM) and the Parenting Relationship in Children Born very Preterm. (October 2012) - Pritchard, MA; Crothers, C; Dassel, T de; Johnston, L; Beller, E; Bogossian, F; Callan, S; Colditz, PB; Russo, S; Cartwright, D
Abstract : Background/aim: Differences in parenting children born very-preterm (VPT < 29 weeks gestation) with and without developmental delay has not been fully described. This study examines the association between parent-reported child developmental status, psychosocial-risk and the parenting-relationship in VPT children. Methods: Cross-sectional hospital-cohort of infants at 2 and 4-years corrected age for prematurity during 2010. Uni-multivariate analysis examined the association between developmental delay (DD) (scores -≥2SD in ≥2 domains-gross/fine motor, receptive/expressive language, social-emotional and self-help using Parent Evaluations of Developmental Status-Developmental Milestones-(PEDS:DM)-Assessment-Level) and parenting-relationship (score -≥1SD in ≥1 domain-attachment, involvement, discipline-practices, parenting confidence and relational frustration assessed by the Parenting Relationship Questionnaire). Outcomes are for the total cohort and by age-group, adjusted for psychosocial-risk (≥4/11 risks on Brigance Observations of Psychosocial-Risk Scale). Results: Cohort data is available on 165/192, 86% (2-years, N=80; 4-years, N=85) children which showed parenting a child with DD was associated with higher parenting-relationship problems for the total cohort (OR 3.2, 95%CI 1.5, 7.0, p<0.01) who experienced greater difficulties in attachment (OR 3.2, 95%CI 1.1, 10.3, p =0.04) and parenting confidence (OR 4.7, 95%CI, 2.1, 11.5, p<0.01) compared to the non-delayed group. Differences by age group were (2-year-group, attachment; OR 7.3, 95%CI 1.4, 37.0, p =0.02) and (4-year-group, parenting confidence; OR 16.0, 95%CI 4.4, 57.3, p<0.01) found. Conclusion: Mothers of VPT children with DD may require additional parenting support; strengthening early attachment may impact latter parenting confidence in these families. Examining these findings in relation to child behavior and possible pathways for intervention is planned.